2008
DOI: 10.1371/journal.pone.0003706
|View full text |Cite
|
Sign up to set email alerts
|

Bacillus anthracis Peptidoglycan Stimulates an Inflammatory Response in Monocytes through the p38 Mitogen-Activated Protein Kinase Pathway

Abstract: We hypothesized that the peptidoglycan component of B. anthracis may play a critical role in morbidity and mortality associated with inhalation anthrax. To explore this issue, we purified the peptidoglycan component of the bacterial cell wall and studied the response of human peripheral blood cells. The purified B. anthracis peptidoglycan was free of non-covalently bound protein but contained a complex set of amino acids probably arising from the stem peptide. The peptidoglycan contained a polysaccharide that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
60
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(64 citation statements)
references
References 62 publications
4
60
0
Order By: Relevance
“…In the host, B. anthracis remodels its peptidoglycan as suggested by the abundant production of peptidoglycan hydrolases during infection (47). Because purified B. anthracis peptidoglycan stimulates an inflammatory response in vitro (48), controlling the composition of muropeptides shed during multiplication in the host may enable better survival of the pathogen. Indeed, the detection of MurNAc by Nod2, the eukaryotic intracellular muropeptide receptor, is altered by the conversion of MurNAc into anhydro-MurNAc (53).…”
Section: Discussionmentioning
confidence: 99%
“…In the host, B. anthracis remodels its peptidoglycan as suggested by the abundant production of peptidoglycan hydrolases during infection (47). Because purified B. anthracis peptidoglycan stimulates an inflammatory response in vitro (48), controlling the composition of muropeptides shed during multiplication in the host may enable better survival of the pathogen. Indeed, the detection of MurNAc by Nod2, the eukaryotic intracellular muropeptide receptor, is altered by the conversion of MurNAc into anhydro-MurNAc (53).…”
Section: Discussionmentioning
confidence: 99%
“…B. anthracis EF, LF, and PA were purchased from List Biological Laboratories (Campbell, CA). B. anthracis Sterne BaPGN was isolated as described previously (20,21). Fluorochrome-conjugated antibodies to human proteins and other flow cytometry-related items were purchased from the following vendors: anti-human CD3 (phycoerythrin [PE]-Alexa Fluor 610) and CD19 (allophycocyanin [APC]-Alexa Fluor 750) and Pacific blue-conjugated streptavidin from Invitrogen, Carlsbad, CA; anti-human CD16b (fluorescein isothiocyanate [FITC]) from GeneTex, Irvine, CA; anti-human CD14 (peridinin chlorophyll protein [PerCP]-Cy5.5), IL-1␣ (FITC), IL-1␤ (PE), TNF-␣ (PE-Cy7), IL-6 (Alexa Fluor 700), and brefeldin A from eBioscience, San Diego, CA; biotin-conjugated anti-human CD16b from Exbio, San Diego, CA; anti-human MIP-1␤ (PE-Cy7) from BD Pharmingen, San Diego, CA; anti-human IL-8 (APC) from BioLegend, San Diego, CA; anti-human GRO-␣ (PE), MIP-1␣ (APC), and anthrax toxin receptor 2 (ANTXR2/CMG2) and APC-conjugated streptavidin from R&D Systems, Minneapolis, MN; anti-human TEM8/ANTXR1 from Abcam, Cambridge, MA; and recombinant human GRO-␣ (CXCL1), CXCL10 (IP-10), and MCP1 (CCL2) from PeproTech, Rocky Hill, NJ.…”
Section: Methodsmentioning
confidence: 99%
“…In the case of B. anthracis, peptidoglycan (BaPGN) is released during growth in blood and has been shown to be a pathogen-associated molecular pattern (PAMP) (20). Further, we have shown that highly purified BaPGN activates the p38 MAPK pathway in monocytes (20,21), and BaPGN polymers are taken up by mononuclear cells, causing monocytes to produce interleukin 8 (IL-8), tumor necrosis factor alpha (TNF-␣), IL-6, and IL-1␤ (20,22). Thus, BaPGN is detected by monocytes and, upon phagocytosis, triggers a response that could assist in clearing the organism from the host.…”
mentioning
confidence: 97%
“…At nonmucosal sites like vasculature, PGN is recognized by Toll-like receptors (TLRs) expressed by immune cells (e.g. macrophages) (Yoshimura et al, 1999), which triggers intracellular signal transduction pathways, resulting in the production of pro-infl ammatory cytokines (Langer et al, 2008) and chemokines (Wang et al, 2000). Since PGN is presumed to be an additional proinfl ammatory factor in atherosclerotic lesions (Laman et al, 2002), elucidation of the mechanism of action of PGN-induced infl ammatory responses will broaden current knowledge of the roles of bacterial PAMPs in atherogenesis.…”
Section: Original Articlementioning
confidence: 99%